The Gospel of Matthew in its Roman Imperial Context. - Riches, John K. (Library of New Testament studies., 2005)
In what sense does Matthew''s Gospel reflect the colonial situation in which the community found itself after the fall of Jerusalem and the subsequent humiliation of Jews across the Roman Empire? To what extent was Matthew seeking to oppose Rome''s claims to authority and sovereignty over the whole world, to set up alternative systems of power and society, to forge new senses of identity? If Matthew''s community felt itself to be living on the margins of society, where did it see the centre as lying? In Judaism or in Rome? And how did Matthew''s approach to such problems compare with that.